Adipocyte commitment of 3T3-L1 cells is required to support human adenovirus 36 productive replication concurrent with altered lipid and glucose metabolism - Márquez, Verónica; Ballesteros, Grisel; Dobner, Thomas; González, Ramón A. (Frontiers in Cellular and Infection Microbiology, 2022)
Human adenovirus 36 (HAdV-D36) can cause obesity in animal models, induces an adipogenic effect and increased adipocyte differentiation in cell culture. HAdV-D36 infection alters gene expression and the metabolism of the infected cells resulting in increased glucose internalization and triglyceride accumulation. Although HAdV-D36 prevalence correlates with obesity in humans, whether human preadipocytes may be targeted in vivo has not been determined and metabolic reprogramming of preadipocytes has not been explored in the context of the viral replication cycle. HAdV-D36 infection of the mouse fibroblasts, 3T3-L1 cells, which can differentiate into adipocytes, promotes proliferation and differentiation, but replication of the virus in these cells is abortive as indicated by short-lived transient expression of viral mRNA and a progressive loss of viral DNA. Therefore, we have evaluated whether a productive viral replication cycle can be established in the 3T3-L1 preadipocyte model under conditions that drive the cell differentiation process. For this purpose, viral mRNA levels and viral DNA replication were measured by RT-qPCR and qPCR, respectively, and viral progeny production was determined by plaque assay. The lipogenic effect of infection was evaluated with Oil Red O (ORO) staining, and expression of genes that control lipid and glucose metabolism was measured by RT-qPCR. In the context of a viral productive cycle, HAdV-D36 modulated the expression of the adipogenic genes, C/EBPα, C/EBPβ and PPARγ, as well as intracellular lipid accumulation, and the infection was accompanied by altered expression of glucolytic genes. The results show that only adipocyte-committed 3T3-L1 cells are permissive for the expression of early and late viral mRNAs, as well as viral DNA replication and progeny production, supporting productive HAdV-D36 viral replication, indicating that a greater effect on adipogenesis occurs in adipocytes that support productive viral replication.